모과나무 잔가지에서 분리한 국내 미기록 점균류 Chaenomeles sinesis 보고 - 안금란; Geum Ran Ahn; 김보영; Bo Young Kim; 윤여홍; Yeo Hong Yun; 손승렬; Seung Yeol Son; 김성환; Seong Hwan Kim (Hangug gynnhaghoi ji, 2016)
Chaenomeles sinensis, called as Chinese quince, belongs to the family Rosaceae and is widely distributed in Korea, China, and Japan. A microorganism was isolated from part of a twig of C. sinensis that showed an abnormal appearance. The microorganism was identified as the slime mold Stemonaria longa of the division Myxomycota, which was previously unrecorded in Korea. The present study reports the morphological characteristics of the isolated fungus and a phylogenetic relationship based on the β-tubulin gene sequences.